Evaluating Outcome Measures in Veterinary Physiotherapy with Particular Reference to the Treatment of Canine and Equine Joint Cases - Brookes, William (2023)
Background: Veterinary physiotherapists provide postoperative care, rehabilitation, sports maintenance, and aged maintenance for their patients. Outcome measures are extensively used within human medicine, including physiotherapy, but a widely accepted issue in veterinary physiotherapy practice is that outcome measures lack sufficient evaluation with regard to intra- and inter-clinician comparisons. This project aimed to determine the quality of outcome measures being used in canine and equine physiotherapy practice and any disparities external factors cause. Methods: A structured scoping literature review consolidated current understanding and limitations. This was combined with a survey of qualified veterinary physiotherapists (n=40). Statistical analysis comprised descriptive statistics and Chi Squared analyses. Results: Key observations generated include (1) a lack of differences in application of outcome measures between veterinary physiotherapists with and without a human physiotherapy background, (2) enhanced utilisation of outcome measures by members of a registration body and (3) an overall skew towards subjective, rather than objective, outcome measure use. Limitations: Sample size and time for a secondary survey further exploring limitations. Conclusion: Recommendations on enhancing outcome measures in clinical practice include several technical measures, e.g. goniometers and pain scoring, and profession-wide initiatives, including the introduction of comprehensive CPD resources and reviews of regulatory and education bodies.